MCTS : Windows Server 2008 active directory configuration study guide - Panek, William, 1970- (Wiley, 2008)
"With Microsoft's release of Windows Server 2008 and a new generation of certification exams, IT administrators have more reason than ever to certify their expertise in the world's leading server software. Inside, find the full coverage you need to prepare for Exam 70-640: Windows Server 2008 Active Directory, Configuring, one of three specializations in the Microsoft Certified Technology Specialist (MCTS) certification track. You'll find full coverage of all exam objectives, practical exercises, real-world scenarios, challenging review questions, and more"--Resource description page